93.3k views
7 votes
(x+y)(x-y) if x=-3 and y=-5

User Inteloid
by
5.2k points

2 Answers

1 vote

Answer:

-16

Explanation:

As we have


{x}^(2) - {y}^(2) = (x + y)(x - y)

Here

x= -3

y= -5

Subtitute x and y


{x}^(2) - {y}^(2) \\ ( - 3{)}^(2) - ( - 5 {)}^(2) \\ 9 - 25 \\ - 16

User Shaun McHugh
by
4.9k points
8 votes

Answer:

-16

Explanation:

We first need to substitute

Since x = -3 and y = -5

(-3+-5)(-3 - -5)

Let's Solve (-3+-5)

which = -8

Then Solve (-3 - -5)

which = 2

Now -8 × 2 = -16

Hence, Answer = -16

~Lenvy~

User Amruth
by
5.6k points